The Aspect of Shenyang Normal University's Undergraduate: Thesis on Music Performance Study - Wang Xu; Pramote Danpradit (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
This paper employed document analysis of specific thesis studies in musical instrument performance majors at Shenyang Normal University.The aim of this study was to study perspectives on topic selection, diversity, literature review, presentation ability, and thesis format.Thesis scope studies were chosen between 2016 and 2021.The thesis comprehensive bachelor's and master's thesis 116 as an analysis object, forming undergraduate students of 163 and 26 postgraduate students, totalling 189. On the basis of this research, it was found that the title and content were in a narrow group focusing on music practice studies, an initial analysis of music after developing knowledge integration and innovation, research literacy skills, and a thesis, which directly affected the title to the format of the thesis book, with factors affecting in terms of choosing a major, the level of understanding of the advisors, the importance of educational institutions, lack of relevant courses, students' educational level, students' writing attitude, and various observations were requested to be developed into criteria for evaluating music thesis and curriculum reform and music thesis experiment in order to be a manual for writing science in the future and contribute to the problems found as well as additional research by the authors and other experts.